Anode characteristics of Al/Ti galvanic couple in a salt spray environment. Issue 12 (3rd September 2019) - Zou, Shiwen; Qu, Yichao; Zhou, Wenlong; Xu, Wen; Fu, Xuesong
Abstract: The galvanic corrosion behavior of a 2A12 aluminum alloy and a Ti‐15‐3 titanium alloy in a salt spray environment was investigated. The results indicated that the galvanic effect accelerated the dissolution rate of the anodes significantly; however, the corrosion of the anode was not uniform. The region adjacent to the coupled joint experienced the most significant corrosion, with galvanic corrosive action emerging as dominant. The corrosion of the region distant from the joint was slight and was dominated by the self‐corrosion process. A new model for the current difference distribution of the galvanic couple was established to illuminate the nonuniform corrosion phenomenon of the anode. Abstract : The galvanic corrosion behavior of the 2A12 aluminum alloy and Ti‐15‐3 titanium alloy in a salt spray environment was investigated. The results indicated that the galvanic effect accelerated the dissolution rate of the anodes significantly; however, the corrosion of the anode was not uniform. The region adjacent to the coupled joint experienced the most significant corrosion, with galvanic corrosive action emerging as dominant.